Enhancing Financial Literacy and Simple Reporting Skills Among Indonesian Migrant Entrepreneurs In Penang, Malaysia (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The goal of this community service program was to help Indonesian migrant business owners in Penang, Malaysia, learn more about money and how to report it simply. Many small business owners don't keep their business and personal finances separate, use informal financial practices, and don't know much about their tax obligations. These conditions make it harder for them to get formal loans and make their businesses less sustainable. The program was for 75 Indonesian migrant workers and small business owners. It included lectures, discussions, and hands-on tutorials on basic financial management, capital planning, simple bookkeeping, and how to pay taxes on income earned abroad. The evaluation used tests before and after to see how well people understood the goals of financial management, the accounting cycle, sources of capital, how to keep track of transactions in a systematic way, and how to report and pay taxes. The results show a big improvement in the participants' skills, with the average score going up from 37.2 percent to 80.2 percent, or 43.0 percent. The biggest improvement was knowing how to keep track of income and expenses and file taxes and reports. Participants said that the training materials were useful for their daily work and helped them plan their cash flow and keep better records of their transactions. The results indicate that structured financial literacy training can greatly help Indonesian migrant entrepreneurs become better managers and keep their small and micro businesses going.